2004
DOI: 10.1097/01.ccm.0000114829.17746.19
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived exosomes of septic individuals possess proapoptotic NAD(P)H oxidase activity: A novel vascular redox pathway*

Abstract: Platelet-derived exosome NADPH oxidase activity seems to contribute to vascular cell apoptosis and may represent a new vascular redox-signaling pathway involved in the pathophysiology of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
155
0
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(177 citation statements)
references
References 37 publications
5
155
0
10
Order By: Relevance
“…This is consistent with a previous report that the densities of HLA-DR-and CD63-bearing exosomes are 1.23-1.27 g/mL and those of HLA class I-bearing exosomes are 1.15-1.27 g/mL [23]. Based on the findings that CD63 is a major marker protein for activated platelets and the existence of platelet-derived exosomes in human plasma is known [28,29], different populations of exosomes represented by their protein composition might be present as well in human plasma.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with a previous report that the densities of HLA-DR-and CD63-bearing exosomes are 1.23-1.27 g/mL and those of HLA class I-bearing exosomes are 1.15-1.27 g/mL [23]. Based on the findings that CD63 is a major marker protein for activated platelets and the existence of platelet-derived exosomes in human plasma is known [28,29], different populations of exosomes represented by their protein composition might be present as well in human plasma.…”
Section: Discussionsupporting
confidence: 81%
“…MPs can affect endothelial function by altering the balance between NO and reactive oxygen species (ROS) production and release. In this way, it has been reported that MPs decrease endothelial NO-dependent relaxation (eNOS) expression (8) and enhance ROS production (16,17).…”
mentioning
confidence: 99%
“…2017; 16 (4): 94-105 100 в области патофизиологии сепсиса [65][66][67]. Ин-кубация ýндотелиальных клеток и SMCs с тром-боцитарными микрочастицами от септических больных приводит к выраженной индукции апоп-тоза в клетках, в результате выработки активных форм кислорода, что предполагает центральный механизм патогенеза сосудистой дисфункции при сепсисе [66,67].…”
Section: тромбоциты и регенерацияunclassified
“…2017; 16 (4): 94-105 100 в области патофизиологии сепсиса [65][66][67]. Ин-кубация ýндотелиальных клеток и SMCs с тром-боцитарными микрочастицами от септических больных приводит к выраженной индукции апоп-тоза в клетках, в результате выработки активных форм кислорода, что предполагает центральный механизм патогенеза сосудистой дисфункции при сепсисе [66,67]. Как бы то ни было, но доказа-но, что тромбоцитарные микрочастицы способ-ны фосфорилировать и активировать RAC-alpha serine/threonine-protein kinase, protein kinase B alpha (Akt), серин-треониновую киназу, кото-рая инактивирует промоутер смерти, ассоцииро-ванный с B-клеточной лимфомой 2 -RAC-alpha serine/threonine-protein kinase, protein kinase B alpha (BAD) [68], и оказывает антиапоптотиче-скую активность в ТНР-1 клетках, линии клеток моноцитарного лейкоза человека, зависящей от р-селектина [69].…”
unclassified